(untitled) (Fiep Bulletin - online, 2012)
The present study deals with the prevention of childhood obesity and promoting health at school. Among the various methods and procedures used in this direction, stimulation of physical activity has received, perhaps, a greater emphasis among professionals who work in this area. It is believed that the child outside the standard of obesity tends to have better motor performance and better adherence to physical activity. The objective of this study is to establish a comparison between school children obese and nonobese, using psychomotor tests in order to assess their motor skills. We conducted a field study with 16 (sixteen) students, the Colégio Republicano, with chronological age of 8 and 9 years with the support of literature review. Through the analysis of data collected by psychomotor tests revealed a non significant difference between the two groups. Children with excess body fat had the same difficulties as other children, lying on the same level of psychomotor development, which leads us to conclude that childhood obesity is not interference factor in child development.